2019
DOI: 10.3390/ijms20225766
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of Organic Oils Blended Magnetorheological Fluids with the Field-Dependent Material Characterization

Abstract: Automation is one of the trending terminologies in the field of engineering to achieve various sensors and actuators such as the hydraulic system. Smart fluid is also one of the hot topics for researchers to develop a type of actuator in many control systems since the fluid’s rheological characteristics can be controlled or tuned by the intensity of the external stimuli. In this work, a new smart fluid of magnetorheological (MR) fluid is proposed and its field-dependent rheological characteristics are experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 19 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…Sedimentation can be caused by the density mismatch between SPIONs@OA and oil, although the stability is much higher in comparison to other liquids, where the deposition reaches even 60% (Zhang et al 2009, Jinaga et al 2019, Kumar et al 2019.…”
Section: Stability Of Mr Fluidmentioning
confidence: 99%
“…Sedimentation can be caused by the density mismatch between SPIONs@OA and oil, although the stability is much higher in comparison to other liquids, where the deposition reaches even 60% (Zhang et al 2009, Jinaga et al 2019, Kumar et al 2019.…”
Section: Stability Of Mr Fluidmentioning
confidence: 99%
“…Jinaga et al [ 148 ] showed that sedimentation stability, off‐state viscosity, and τ y of MRFs could be further improved by blending silicon oil, honey with cottonseed oil (20.13 kPa), and Su (17.73 kPa). In a similar study with EI and CI, Vannarth et al [ 149 ] prepared MRFs using natural mahua oil (MO) and simarouba oil (SO) extracted by cold pressing.…”
Section: Mrf With Different Carrier Fluidsmentioning
confidence: 99%
“…The same behavior is observed for the shear stress of MRF that increases with the applied external magnetic field until becoming field-independent. MRF is usually made of ferromagnetic, ferrimagnetic, or superparamagnetic colloidal suspension dispersed in liquid media like oil (Elizabeth Premalatha et al, 2012; Galindo-Gonzalez et al, 2016; Jinaga et al, 2019; Zhu et al, 2019), so the magnetic properties of the MRF depend on magnetization. Although MRF reveals the ability to respond rapidly to the magnetic field, they tend to sediment, decreasing their long-term stability (Park et al, 2009; Prajapati and Lakdawala, 2022; Wereley et al, 2006).…”
Section: Introductionmentioning
confidence: 99%